Focus on Therapeutic Strategies of Nonalcoholic Fatty Liver Disease. (8th November 2012) - Durazzo, Marilena; Belci, Paola; Collo, Alessandro; Grisoglio, Enrica; Bo, Simona
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the Western world (it affects 30% of the general adult population). The NAFLD encompasses a histological spectrum ranging from simple steatosis to nonalcoholic steatohepatitis (NASH), defined by steatosis, hepatocellular damage, and lobular inflammation in individuals without significant alcohol consumption and negative viral, congenital, and autoimmune liver disease markers. Currently, NAFLD is considered an emerging epidemic in light of the dramatic increase in obesity rates. With the progressive nature of NASH and its rising prevalence there is a significant need for a specific and targeted treatments since to date there has not been any validated therapies for NAFLD other than weight loss, which is well known to have a poor long-term success rate. In recent years, visceral adipose tissue has taken an important role in NAFLD pathogenesis, and current therapeutic approaches aim at reducing visceral obesity and free fatty acid overflow to the liver. This paper is focused on the treatments used for NAFLD and the potential new therapy.